2014
DOI: 10.1039/c3sc53414f
|View full text |Cite
|
Sign up to set email alerts
|

Non-directed allylic C–H acetoxylation in the presence of Lewis basic heterocycles

Abstract: We outline a strategy to enable non-directed Pd(II)-catalyzed C–H functionalization in the presence of Lewis basic heterocycles. In a high-throughput screen of two Pd-catalyzed C–H acetoxylation reactions, addition of a variety of N-containing heterocycles is found to cause low product conversion. A pyridine-containing test substrate is selected as representative of heterocyclic scaffolds that are hypothesized to cause catalyst arrest. We pursue two approaches in parallel that allow product conversion in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 63 publications
3
43
0
Order By: Relevance
“…Accordingly, Malik et al tested two established Pd-catalyzed allylic acetoxylation protocols, either on a model terminal alkene in the presence of N-heterocycles, or on terminal alkenes incorporating a pyridine ring. [53] The study confirmed that both protocols are strongly affected by the presence of Lewis basic moieties. However, satisfactory conversion can be restored by two strategies: (a) addition of a Lewis acid such as BF 3 ·Et 2 O, and (b) prior conversion of the pyridine moiety into the corresponding pyridine N-oxide.…”
Section: Aerobic Conditionssupporting
confidence: 57%
“…Accordingly, Malik et al tested two established Pd-catalyzed allylic acetoxylation protocols, either on a model terminal alkene in the presence of N-heterocycles, or on terminal alkenes incorporating a pyridine ring. [53] The study confirmed that both protocols are strongly affected by the presence of Lewis basic moieties. However, satisfactory conversion can be restored by two strategies: (a) addition of a Lewis acid such as BF 3 ·Et 2 O, and (b) prior conversion of the pyridine moiety into the corresponding pyridine N-oxide.…”
Section: Aerobic Conditionssupporting
confidence: 57%
“…Subsequent studies have shown that DAF is uniquely effective in a number of other Pd-catalyzed aerobic oxidation reactions, including oxidative C–C and C–O coupling reactions with arenes, 18 α,β-dehydrogenation of cyclic ketones, 19 oxidative Heck reactions, 20 and also various non-aerobic oxidation reactions. 21 …”
Section: Introductionmentioning
confidence: 99%
“…[4] Overcoming such strongc helation by heterocycles containing N, O, Pa nd Si sa nu phill task, and only few examples are known in the literature to surpass this issue (Scheme 1a). [6] Recently,Y ua nd co-workerse xemplified the remarkable yets elective synthesis of heterocyclesc atalyzed by Pd 0 using anionic NÀOMe as aw eakly chelating directing group in the presenceo fo ther heterocycles (Scheme 1b). [6] Recently,Y ua nd co-workerse xemplified the remarkable yets elective synthesis of heterocyclesc atalyzed by Pd 0 using anionic NÀOMe as aw eakly chelating directing group in the presenceo fo ther heterocycles (Scheme 1b).…”
mentioning
confidence: 99%